Moisture transport and seasonal variations in the stable isotopic composition of rainfall in Central American and Andean Páramo during El Niño conditions (2015–2016) - Esquivel-Hernández, Germain (2019)
High‐elevation tropical grassland systems, called Páramo, provide essential ecosystem services such as water storage and supply for surrounding and lowland areas. Páramo systems are threatened by climate and land use changes. Rainfall generation processes and moisture transport pathways influencing precipitation in the Páramo are poorly understood but needed to estimate the impact of these changes, particularly during El Niño conditions, which largely affect hydrometeorological conditions in tropical regions. To fill this knowledge gap, we present a stable isotope analysis of rainfall samples collected on a daily to weekly basis between January 2015 and May 2016 during the strongest El Niño event recorded in history (2014–2016) in two Páramo regions of Central America (Chirripó, Costa Rica) and the northern Andes (Cajas, south Ecuador). Isotopic compositions were used to identify how rainfall generation processes (convective and orographic) change seasonally at each study site. Hybrid Single Particle Lagrangian Integrated Trajectory model (HYSPLIT) air mass back trajectory analysis was used to identify preferential moisture transport pathways to each Páramo site. Our results show the strong influence of north‐east trade winds to transport moisture from the Caribbean Sea to Chirripó and the South American low‐level jet to transport moisture from the Amazon forest to Cajas. These moisture contributions were also related to the formation of convective rainfall associated with the passage of the Intertropical Convergence Zone over Costa Rica and Ecuador during the wetter seasons and to orographic precipitation during the transition and drier seasons. Our findings provide essential baseline information for further research applications of water stable isotopes as tracers of rainfall generation processes and transport in the Páramo and other montane ecosystems in the tropics